Reading Indonesian and Malaysian Young Adult Novels: Capturing the Image of Young Muslim Women in Indonesia and Malaysia - Nor Ismah (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
A number of novel remaja, which mean young adult novels, written by women writers from Indonesia and Malaysia have been published. Writing competitions held by book publishers and language centers have also encouraged the production of the novels. However, since they address youth as their readers and tend to consider the characters, issues, language, and values that appeal to the modern young adult; therefore, some critics say that the novels only respond to the demands of the reader market and they are less creative and lack of quality. In this paper I demonstrate the value of Indonesian and Malaysian novel remaja by examining four novels which are Siti Zaleha M. Hashim’s Biarkan Kupu-Kupu Terbang (“Let the Butterfly Fly”), Rumah Cinta Kelana (“The Love House of Kelana”), written by Sofie Dewayani, Nisah Haron’s Mencari Locus Standi (“Finding the Defense Locus”), and Jadilah Purnamaku Ning written by Khilma Anis. I argue that those novels do not only explore young adults’ feelings, including romance, fear, sadness, happiness, and challenges, but they also describe important themes which may inspire young readers, such as how young Muslim women deal with their identity formation, living in a single mother family, and polygamy. Novel-novel remaja karya penulis perempuan banyak diterbitkan di Indonesia dan Malaysia. Lomba menulis yang diadakan oleh penerbit buku dan pusat bahasa juga mendorong banyaknya produksi novel-novel tersebut. Namun, karena novel remaja menyasar remaja sebagai pembacanya, novel tersebut ditulis dengan mempertimbangkan karakter, isu, bahasa, dan nilai-nilai yang menarik bagi remaja modern. Sehingga, beberapa kritikus mengatakan bahwa novel remaja hanya menjawab tuntutan pasar pembaca dan kurang kreatif serta berkualitas. Tulisan ini bertujuan untuk menunjukkan nilai positif novel remaja yang terbit di Indonesia dan Malaysia dengan menelaah empat novel. Yaitu, Biarkan Kupu-Kupu Terbang karya Siti Zaleha M. Hashim, Rumah Cinta Kelana yang ditulis oleh Sofie Dewayani, Mencari Locus Standi karya Nisah Haron, dan Jadilah Purnamaku Ning yang ditulis oleh Khilma Anis. Saya berpendapat bahwa novel-novel tersebut tidak hanya mengeksplorasi perasaan remaja, termasuk percintaan, ketakutan, kesedihan, kebahagiaan, dan tantangan hidup, tetapi juga menggambarkan tema-tema penting yang dapat menginspirasi pembaca remaja. Misalnya, tema tentang bagaimana remaja Muslim perempuan menjalani proses pembentukan jati diri, hidup bersama keluarga dengan ibu tunggal, dan poligami, bahkan juga mengkritisi ketimpangan posisi perempuan di dalam masyarakat.